Answer:
(E) √[2q/m(Vs - VT)]
Step-by-step explanation:
Since the charge -q moves from VT to VS, the potential difference is VT - VS.
The work done in moving the charge q across a potential difference V is given by W = qV.
Now, the work done in moving the charge -q across that potential difference VT - VS is thus W = -q(VT - VS) = -q[-(VS - VT)] = q(VS - VT). This work equals the sphere's kinetic energy and kinetic energy equals K = 1/2mv² where m = mass of sphere and v = speed of sphere.
So, K = W
1/2mv² = q(VS - VT)
v² = 2q/m(VS - VT)
taking square root of both sides, we have
v = √[2q/m(Vs - VT)]